Field evaluation of advanced rice lines for adaptability to drought and heat in the Senegal River Valley - Moukoumbi, Y.D.; El-Namaky, R.; Sikirou, M.; Bocco, R.; Mbodj, D.; Pegalepo, E.; Akueson, A.H.G.; Manneh, B. (2025)
In Senegal, the average rice consumed is 100 kg per capita per year. The objective was to evaluate and select the well‐adapted high‐yielding lines in Ndiaye and Fanaye growth conditions in Senegal River Valley. One hundred and twelve advanced lines were evaluated in consecutive wet and dry seasons at AfricaRice Fanaye and Ndiaye sites challenged by drought and high temperatures. Unlike Fanaye, Ndiaye faces severe water scarcity and extreme heat. An alpha‐lattice design was used with three replications. The number of tillers and plant height at 30 days after sowing, plant height at maturity, days to 50% heading, and grain yield; physiological: leaves chlorophyll content at 50% heading stage, yield grain, thousand grain weight, and number of panicles per plant were recorded to evaluate the increasing of rice productivity. Results showed significant variation among the advanced lines and the test “Kruskal‐Wallis medians” was used for the mean comparison for the five descriptors during growth and development stages. Path analysis revealed that Ndiaye's harsh conditions negatively impacted NT30, PH30, PHmat, PNP, Dmat, and GY, with negative effects on NT30 (ρ = −0.63), PH30 (ρ = −0.67), and PNP (ρ = −0.15). However, SH (ρ = 0.71) and TGW (ρ = 0.37) had positive direct effects. Cluster analysis generated four groups showing the characteristics of 112 advanced lines. Most of the advanced lines were outperforming local elite varieties. The lines WAC 18‐WAT15‐3‐1, WAC 18‐WAT65‐1‐1, WAC 13‐WAT32‐2‐1, and WAB 2150‐TGR1‐WAT3‐1 produced the highest yields for Ndiaye, with 4752, 5589, 5589, 5644, and 6943 kg/ha. For Fanaye, the best genotypes were IR 09 N523, CT18919‐4‐2‐2‐2SR‐1P, CT18494‐4‐4‐3‐3‐1SR, WAB 2125‐WACB‐1‐TGR1‐WAT1‐1, and CT19541‐13‐3‐1‐2P‐3P, with 8824, 8984, 9014, 9639, and 8496 kg/ha, respectively. The authors recommend that these lines be released or used as donors in breeding programs, and further studies can consider stability analysis using the best adapted varieties.